Students Attitude Towards LGBTQ; the Future Counselor Challenges - Zadrian Ardi; Frischa Meivilona Yendi; Ifdil Ifdil (Indonesian Institute for Counseling, Education and Therapy (IICET), 2017)
The condition of sexual disorientation behavior is a condition that develops from various and interrelated factors. This behavior is not the result of a single major factor, its formation occurs throughout the individual life span instead. The sexual behavior disorientation is a phenomenon that is always happening almost in all communities in various countries, which in the modern world popular with the term LGBTQ (Lesbian, Gay, Bisexual, Transgender and Queer). Another condition related to this community is that in recent years human rights related to this matter have been straightforwardly defended in some countries. This condition brings many problems and polemics in various dimensions of life. This study focuses on the trend of student attitudes toward LGBTQ phenomena that in the society. Data were collected through a student's attitude scale on the LGBTQ phenomenon adapted from